Hard switching‐based hybrid RF/VLC system and its performance evaluation. Issue 2 (16th September 2018) - Gupta, Akash; Garg, Parul; Sharma, Nikhil
Abstract: In this paper, we investigate the performance of hard switching‐based radio frequency/visible light communication (RF/VLC) downlink system, for indoor wireless communication system. The proposed system exploits the advantages of VLC and RF system, ie, high data rate transmission by VLC and pervasive coverage by RF. The indoor RF link is considered to be Nakagami‐m fading channel while the VLC links are subjected to statistical channel model based on the uniformly distributed end user position. In this paper, we study the performance of hybrid RF/VLC system in terms of outage probability, average bit error rate, ergodic capacity, packet error rate, and throughput. Furthermore, we compare the results of proposed RF/VLC system with stand‐alone VLC system to prove its effectiveness. The results prove that, for lower values of average signal‐to‐noise ratio, the proposed system outperforms the stand‐alone VLC system. Abstract : We present a hard switching‐based radio frequency/visible light communication (RF/VLC) downlink system, for indoor wireless communication system. The performance of hybrid RF/VLC system is analyzed in terms of outage probability, average bit error rate, ergodic capacity, packet error rate, and throughput. Furthermore, we compare the results of proposed RF/VLC system with stand‐alone VLC system to prove its effectiveness.